Numerical fault simulation in Himalayas with 2 D finite element method - Howladar, M. Farhad; Hayashi, Daigoro (National Institute of Polar Research, 2003)
P(論文) The nature of the stress field in the Himalaya is examined by the 2D finite element method where linear elastic rheology and plain strain condition are assumed. The Mohr-Coulomb failure criterion has been adopted to analyze the relationship between stress distribution and fault formation.Two profile models are prepared and convergent displacement is imposed on them along the NE-SW horizontal direction.The convergent displacement and physical properties of the rock layer control the distribution,orientation,magnitude and intensity of the stress and fault development.According to the calculated stress pattern,thrust faults are expected to develop in the central Himalaya (model A).Normal and some thrust faults take place in the north-western Himalaya (model B).The results from our numerical experiment are in agreement with those from the seismicity and focal mechanism solution of earthquakes and also with those of M.M.Alam and D.Hayashi (Bull.Fac.Sci.Univ. Ryukyus, 73, 15, 2002) in the central Himalaya. departmental bulletin paper